Relationship between anthropometric characteristics and ball velocity in elite adolescent handball players - Noutsos, K.; Meletakos, P. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The performance evolution of handball players needs to be studied in many areas such as anthropometric characteristics and ball velocity. The purpose of this study was to investigate the effects of anthropometric characteristics on ball velocity in handball.